2017
DOI: 10.11114/jets.v5i6.2366
|View full text |Cite
|
Sign up to set email alerts
|

Improving Care of Critically Unwell Patients through Development of a Simulation Programme in a Malawian Hospital

Abstract: Introduction: Malawi is one of the world's poorest countries with very limited healthcare spending and a lack of post-graduate training for healthcare workers, including in critical illness management. Critical illness simulation courses have been shown to be an effective training tool and form a key part of training for healthcare professionals in the developed world. However, these courses can be difficult and costly to set. We therefore developed an affordable and simple to run programme for use in a region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The participants considered the training relevant and expressed satisfaction with the content and approach. The significant increase in the participants' overall competence and scores on three domains of competence; knowledge, skill and experience after the training is consistent with the outcome of similar training programmes in critical care settings in Malawi and other developing countries 16,19,[28][29][30] .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The participants considered the training relevant and expressed satisfaction with the content and approach. The significant increase in the participants' overall competence and scores on three domains of competence; knowledge, skill and experience after the training is consistent with the outcome of similar training programmes in critical care settings in Malawi and other developing countries 16,19,[28][29][30] .…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, the study by Barnes and Paterson-Brown 16 which was conducted in Malawi reported significant improvement in the nurses' confidence in the management of critical illness after a training intervention. However, there was minimal increase in the scores on attitude and value domain of ICCN-CS-1 in the present study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There are no training programs specific for critical care nurses in Malawi. This is in contrast to middle and high-income countries where post-registration critical care nursing programs are prevalent7. At the time of data collection, there were less than 10 nurses who had been formally trained in critical care nursing outside the country.…”
Section: Discussionmentioning
confidence: 95%
“…The lack of competent staff including nurses is considered one of the biggest challenges6. The lack of competent staff could possibly be attributed to the lack of training programs specific for critical care nurses in developing countries like Malawi7.…”
Section: Introductionmentioning
confidence: 99%